2021
DOI: 10.1002/pls2.10037
|View full text |Cite
|
Sign up to set email alerts
|

In situ encapsulation of praziquantel through methyl methacrylate/diethylaminoethyl methacrylate and MMA/DMAEMA miniemulsion copolymerizations in presence of distinct ionic surfactants

Abstract: Schistosomiasis is a neglected tropical disease that affects primarily the poorest and most vulnerable populations. Although praziquantel (PZQ) is the drug used most frequently for treatment of schistosomiasis, PZQ presents unpleasant bitter taste and low solubility in water, which prejudice the implementation of pediatric treatments. For this reason, the main purpose of the present work was the production of stable nanoparticles loaded with PZQ through in situ miniemulsion copolymerizations of methyl methacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
3
9
0
Order By: Relevance
“…In this context, the slight reduction in entrapment efficiency of smart microparticles can be explained by the increase in hydrophilicity of the organic phase as a result of the presence of hydrophilic cationic comonomers [41]. In general, the obtained results are consistent with the literature [18,[20][21][22].…”
Section: Entrapment Efficiencysupporting
confidence: 88%
See 3 more Smart Citations
“…In this context, the slight reduction in entrapment efficiency of smart microparticles can be explained by the increase in hydrophilicity of the organic phase as a result of the presence of hydrophilic cationic comonomers [41]. In general, the obtained results are consistent with the literature [18,[20][21][22].…”
Section: Entrapment Efficiencysupporting
confidence: 88%
“…Figure 2 shows the release profiles of PZQ from the different polymer matrices. As expected, the protonation of the comonomers at lower pH values led to swelling of the particles and faster release of the drug, as reported previously for other microscopically dispersed systems [6,22,[42][43][44]. It is important to mention that the smart microparticles exhibited PZQ release rates that were higher than the ones observed for PMMA nanoparticles, emphasizing the existence of chemical and physicochemical characteristics that can balance the presumably higher diffusional resistance offered by the larger microparticles.…”
Section: Dissolutionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, a pharmacokinetic study on rats showed improved bioavailability of the drug encapsulated in the NPs compared to a suspension of HPCT, which is promising for the use these NPs as oral drug delivery nanocarriers. Styrene (S) and MMA-based matrices are commonly used for the entrapment of hydrophobic active ingredients [87][88][89][90][91][92] via direct miniemulsion polymerization at high solids content (around 10-20 wt %), using AIBN or KPS as initiator. As discussed previously, a comonomer can be introduced to adjust the hydrophilicity of the polymer matrix and improve the EE.…”
Section: Miniemulsion Polymerizationmentioning
confidence: 99%